Biorational Control of Callosobruchus maculatus (Coleoptera: Buchidae) in Stored Grains with Botanical Extracts. (29th August 2022) - Akbar, Rasheed; Khan, Imtiaz Ali; Faheem, Brekhna; Azad, Rashid; Zaman, Maid; Altaf, Rubab; Usman, Amjad; Fawad, Muhammad; Farid, Abid; Saljoqi, Ahmad Ur Rahman; Syed, Asad; Bahkali, Ali H.; et al.
Abstract : Globally, around 2000 plant species are used against pest control. The utilization of botanicals is considered the most economic and biodegradable methods for the control of stored grains pests. Therefore, the current study was carried out to investigate the repellency potential of five botanicals against Callosbruchus maculatus F. in Haripur, Pakistan. The concentrations of Azadirachta indica L., Nicotiana tabacum L., Melia azedarach L., Nicotiana rustica L., and Thuja orientalis L. were, i.e., 0.5, 1.0, 1.5, 2.0, 2.5, and 3.0% in four replicates to establish contact effects. The data were recorded after 1, 2, 3, 6, 24, 48, 72, and 96 hours. The repellency effect of these plant species against C. maculatus were increased in both the time- and dose-dependent manner, and highest effect was observed at 72 h. In addition, the repellency effect was 91% for A. indica (class: V), 86% M. azedarach, 82%, N. tabacum (class: V), 79% N. rustica (class: IV), and 75% T. orientalis (class: IV) at 3% concentration against C. maculatus . Furthermore, following 96 hours' exposure to treatment the sensitivity response of insects decreases as the time interval increases, i.e., 86% A. indica (class: V) was followed by 71% M. azedarach (class: IV), 65% N. tabacum (class: IV), 61% N. rustica (class: IV), and T. orientalis 57% (class: III) repellency at highest concentration of 3%. The current study concluded that A. indica and M. azedarach can be incorporated for the management of C. maculatus and these plant species might be helpful in the productions of new biopesticides.